2001
DOI: 10.1177/009102600103000207
|View full text |Cite
|
Sign up to set email alerts
|

What Race Am I? The Need for Standardization in Race Question Wording

Abstract: The goal of the current research was to compare differences in the wording and options of race and ethnic identification items currently in use on employment application forms. Researchers presented subjects with the differentially worded ethnic and race items from two companies and the U.S. Census in an effort to determine if such wording differences would result in different racial classifications. Shifts in racial identification were most notable when race and Hispanic descent were ascertained with two sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, we found that within countries, classificatory metadata change was the norm; the category options evolving from one decade's census to the next. The options and terminology available in the metadata (Kilty & Videl de Haymes, 2004) and the wording of questions (Kirnan et al, 2001) are debated and change over time (Thompson, 2020). As we know from social science methodology, the Posters design of a form and the exact phrasing of questions can affect the results that are obtained; an issue that applies not just to research but to the design of government forms.…”
Section: Preliminary Findings Racial Categories Are Continually Changingmentioning
confidence: 99%
“…Moreover, we found that within countries, classificatory metadata change was the norm; the category options evolving from one decade's census to the next. The options and terminology available in the metadata (Kilty & Videl de Haymes, 2004) and the wording of questions (Kirnan et al, 2001) are debated and change over time (Thompson, 2020). As we know from social science methodology, the Posters design of a form and the exact phrasing of questions can affect the results that are obtained; an issue that applies not just to research but to the design of government forms.…”
Section: Preliminary Findings Racial Categories Are Continually Changingmentioning
confidence: 99%
“…Fredman (2001) draws attention to serious limitations, but seeing the duty placed on public bodies in the UK as being very positive. Kirnan et al (2001) ask if the wording used in questions and response options on application forms and surveys concerning race and ethnicity may be resulting in inconsistent classifications. The variations make comparison difficult.…”
Section: Equal Opportunitymentioning
confidence: 99%